2017
DOI: 10.1007/978-981-10-5657-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Air Pollution and Biomarkers of Health Effect

Abstract: Recently, the air pollution situation of our country is very serious along with the development of urbanization and industrialization. Studies indicate that the exposure of air pollution can cause a rise of incidence and mortality of many diseases, such as chronic obstructive pulmonary disease (COPD), asthma, myocardial infarction, and so on. However, there is now growing evidence showing that significant air pollution exposures are associated with early biomarkers in various systems of the body. In order to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 120 publications
0
29
0
2
Order By: Relevance
“…Air pollutants can invade deep in the lungs and trigger oxidative stress, which in turn causes systemic inflammation. 34 Circulating markers (e.g., cytokines) can pass the maternal-fetal blood barrier and ultimately perturb in utero fetal neurodevelopment. 35,36 Postnatal exposure to fine and ultrafine particulate matter can also affect the CNS through direct translocation along the olfactory nerve into the olfactory bulb, or direct diffusion of induced oxidative stress and inflammatory markers across the impaired blood brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollutants can invade deep in the lungs and trigger oxidative stress, which in turn causes systemic inflammation. 34 Circulating markers (e.g., cytokines) can pass the maternal-fetal blood barrier and ultimately perturb in utero fetal neurodevelopment. 35,36 Postnatal exposure to fine and ultrafine particulate matter can also affect the CNS through direct translocation along the olfactory nerve into the olfactory bulb, or direct diffusion of induced oxidative stress and inflammatory markers across the impaired blood brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Several air pollution studies have suggested that both acute and cumulative exposures to fine PM (PM 2.5 ) may affect cardiac autonomic function, through the alteration of sympathetic and parasympathetic output [24,25,26,27]. In this regard, heart rate variability (HRV), which measures the variation in the time interval between heartbeats, is a noninvasive and sensitive indicator of cardiac autonomic function and has been frequently used to assess the cardiac effects of environmental exposures as a prognostic marker of various forms of cardiovascular diseases (CVDs).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have revealed that in ammation is a key mechanism of human diseases caused by PM exposure. As the main in ammatory cytokines, interleukin (IL) and tumor necrosis factor-alpha (TNF-α) have been widely investigated in epidemiological and biological studies [20][21][22][23][24]. A study focusing on rural India showed that interleukin-6 (IL-6) and TNF-α levels in the serum of individuals from households that used biomass fuels were higher than in those from households that used lique ed petroleum gas (LPG) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al demonstrated a close association between long-term exposure to tra c-related air pollutants and systemic in ammatory markers, such as IL-6 and IL-10 in serum [26]. Furthermore, exposure to air pollutants can disturb toxic pathways and damage human health, such as by inducing oxidative stress [24]. 8-Hydrox-2'-deoxyguanosine (8-OHdG) is a biomarker of oxidative stress and oxidative DNA damage associated with chemical exposure [27], and it is often used to evaluate the oxidative damage caused by personal exposure to air pollutants [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%